2022
DOI: 10.1002/mrd.23647
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones: Metabolism and transportation in the fetoplacental unit

Abstract: The thyroid hormones (THs), thyroxine (T4) and triiodothyronine (T3), are of vital importance for fetal development. The concentration of THs in fetal circulation varies throughout gestation and differs from the concentration in the maternal serum, indicating the presence of maternal‐fetal thyroid homeostasis regulatory mechanisms in the placenta. The passage of THs from maternal circulation to fetal circulation is modulated by plasma membrane transporters, enzymes, and carrier proteins. Monocarboxylate transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 128 publications
(207 reference statements)
0
4
0
Order By: Relevance
“…DIO3 catalyzes the inactivation of T4 to rT3 and of T3 to diiodothyronine (T2), decreasing the levels of T4 and T3. [ 20 , 21 ]. Changes in the expression and activity of DIOs, manifesting as a decrease in DIO2 and an increase in DIO3, under hypoxia and oxidative stress have been described.…”
Section: Discussionmentioning
confidence: 99%
“…DIO3 catalyzes the inactivation of T4 to rT3 and of T3 to diiodothyronine (T2), decreasing the levels of T4 and T3. [ 20 , 21 ]. Changes in the expression and activity of DIOs, manifesting as a decrease in DIO2 and an increase in DIO3, under hypoxia and oxidative stress have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Their presence in human choriocarcinoma cell lines has been known for over 30 years [ 92 ]. More than 15 TH transporters have been identified, but only a fraction of those are involved in placental traffic [ 93 , 94 ]. mRNA sequencing of human placentas showed that L-type Amino-acid Transporters (LAT1 and LAT2), Mono-Carboxylate Transporters (MCT8 and MCT10), and Organic-Anion Transporting Peptides (OATP1A2 and OATP4A1) are the ones playing an active role in transporting TH to the fetus [ 95 ].…”
Section: Physiologic Metabolism During Pregnancymentioning
confidence: 99%
“…T3 regulates the synthesis of endometrial protein mRNAs, including leukemia inhibitory factor (LIF), which is important in the implantation process, and glucose transporter 1 (GLUT-1) ( 122 ). In addition, the placenta has T3 and T4 membrane transporters, DIO2 and DIO3 enzymes that regulate thyroid hormones ( 123 ). Oocytes and embryos cultured in a thyroid hormone-rich medium showed improved blastocyst formation, implantation ability, apoptosis rate, and vitality after cryopreservation ( 124 ).…”
Section: Analysis Of Potential Thyroid-related Etiologies Of Pcosmentioning
confidence: 99%